Semi-guided waves in integrated optical waveguide structures - Ebers, Lena
In dieser Arbeit wird die elektromagnetische Wellenausbreitung in integrierten optischen Wellenleitern mit Hilfe von halb analytischen und numerischen Simulationsmethoden untersucht. Im ersten Teil werden 2-D Si/SiO2-Wellenleiterkonfigurationen mit hohem Brechungsindexkontrast betrachtet. Die Strukturen werden mit halb geführten Wellen unter schrägen Ausbreitungswinkeln angeregt. Dadurch kann die Leistungsübertragung zu bestimmten ausgehenden Moden unterdrückt werden, wodurch vollständig verlustfreie Systeme entstehen. Zusätzlich dient die Anregung mit einem seitlich begrenzten, einfallenden Wellenbündel aus halb geführten Wellen dazu, praktisch relevantere 3-D Konfigurationen zu realisieren. Darüber hinaus wird eine schrittweise Winkelspektrum-Methode vorgestellt, die es ermöglicht, in Kombination mit voll vektoriellen 2-D Finite-Elemente-Lösungen für Teilprobleme mit geringerer Komplexität, die Wellenausbreitung in planaren, linsenförmigen Wellenleitern numerisch in drei Raumrichtungen zu berechnen. Im zweiten Teil dieser Arbeit wird die Ausbreitung in Wellenleiterstrukturen aus Lithiumniobat untersucht, welche für quantenoptische Effekte genutzt werden. Zur Detektion einzelner Photonen werden supraleitende Nanodrähte auf eindiffundierten Lithiumniobat Wellenleitern mit zusätzlicher Taperschicht aus Silizium betrachtet. Um die Wellenausbreitung in diesen 3-D Wellenleitern zu beschreiben, wird eine einseitig gerichtete Finite-Elemente „Modal Matching“ Methode eingeführt. Abschließend werden Rippenwellenleiter aus Lithiumniobat analysiert, die auf Siliziumdioxid Plattformen aufgebracht sind. Der Schwerpunkt liegt hier auf dem nichtlinearen „Parametric Down-Conversion“ Prozess, der für die Erzeugung verschränkter Photonen verwendet wird.
Keywords: tet_topic_waveguide

Finding Optimal Arms in Non-stochastic Combinatorial Bandits with Semi-bandit Feedback and Finite Budget - Brandt, Jasmin; Haddenhorst, Björn; Bengs, Viktor; Hüllermeier, Eyke (arXiv:2202.04487)
We consider the combinatorial bandits problem with semi-bandit feedback under finite sampling budget constraints, in which the learner can carry out its action only for a limited number of times specified by an overall budget. The action is to choose a set of arms, whereupon feedback for each arm in the chosen set is received. Unlike existing works, we study this problem in a non-stochastic setting with subset-dependent feedback, i.e., the semi-bandit feedback received could be generated by an oblivious adversary and also might depend on the chosen set of arms. In addition, we consider a general feedback scenario covering both the numerical-based as well as preference-based case and introduce a sound theoretical framework for this setting guaranteeing sensible notions of optimal arms, which a learner seeks to find. We suggest a generic algorithm suitable to cover the full spectrum of conceivable arm elimination strategies from aggressive to conservative. Theoretical questions about the sufficient and necessary budget of the algorithm to find the best arm are answered and complemented by deriving lower bounds for any learning algorithm for this problem scenario.

Work-in-Progress: The Potential of Interactive Scripts – Supporting Conceptual Understanding and Collaborative Problem-Solving Skills - Temmen, Katrin; Kersten, Peter; Schäfer, Dominik (Mobility for Smart Cities and Regional Development - Challenges for Higher Education)

Reibscheibe für eine Reibungskupplung - Zimmer, Detmar; Blumenthal, Lars Martin; Schadomsky, Magnus
Es ist eine Reibscheibe (18) für eine Reibungskupplung (10) vorgesehen mit einem zwischen Druckplatten (14, 16, 38) verklemmbaren Rotorring (32), Reibbelägen zur Herstellung eines Reibschlusses des Rotorrings (32) mit der jeweiligen Druckplatte, (14, 16, 38), einem axial feststehenden Wellenelement (20) zur Übertragung eines Drehmoments und mindestens einem mit dem Rotorring (32) und mit dem Wellenelement (20) im Wesentlichen drehfest verbundenen und in axialer Richtung elastisch nachgiebigen Federelement (34) zur elastischen axialen Verlagerung des Rotorrings (32) relativ zum Wellenelement (20), wobei der Rotorring (32) zwischen einer Offenstellung, in welcher das Federelement (34) entspannt ist, und einer Schließstellung, in welcher das Federelement (34) von mindestens einer Druckplatte (14, 16, 38) verspannt ist, im Wesentlichen in axialer Richtung parallelverschiebbar ist. Durch den über den vergleichsweise geringen erforderlichen axialen Verlagerungsweg federnd an dem axial unbeweglichen Wellenelement (20) angebundenen die Reibbeläge tragenden Rotorring (32) kann bei geringen Herstellungskosten unnötige Reibung vermieden werden, so dass eine verschleißarme und geräuscharme lösbare Koppelung von Bauteilen ermöglicht ist.

DASC-PM v1.1 - Ein Vorgehensmodell für Data-Science-Projekte - Schulz, Michael; Neuhaus, Uwe; Kaufmann, Jens; Kühnel, Stephan; Alekozai, Emal M.; Rohde, Heiko; Hoseini, Sayed; Theuerkauf, René; Badura, Daniel; Kerzel, Ulrich; Lanquillon, Carsten; Daurer, Stephan; et al.

Size‐Dependent Strain Relaxation in InAs Quantum Dots on Top of GaAs(111)A Nanopillars - Riedl, Thomas; Kunnathully, Vinay S.; Trapp, Alexander; Langer, Timo; Reuter, Dirk; Lindner, Jörg K. N. (Advanced Materials Interfaces)
Keywords: Mechanical Engineering; Mechanics of Materials

Comparative Evaluation of MVAC-LVDC SST and Hybrid Transformer Concepts for Future Datacenters - Huber, Jonas; Wallmeier, Peter; Pieper, Ralf; Schafmeister, Frank; Kolar, Johann (Proc. 9th IEEJ International Power Electronics Conference (IPEC))

Turnpike Property in Optimal Microbial Metabolite Production - Caillau, Jean-Baptiste; Djema, Walid; Gouzé, Jean-Luc; Maslovskaya, Sofya; Pomet, Jean-Baptiste (Journal of Optimization Theory and Applications)
Abstract We consider the problem of maximization of metabolite production in bacterial cells formulated as a dynamical optimal control problem (DOCP). According to Pontryagin’s maximum principle, optimal solutions are concatenations of singular and bang arcs and exhibit the chattering or Fuller phenomenon, which is problematic for applications. To avoid chattering, we introduce a reduced model which is still biologically relevant and retains the important structural features of the original problem. Using a combination of analytical and numerical methods, we show that the singular arc is dominant in the studied DOCPs and exhibits the turnpike property. This property is further used in order to design simple and realistic suboptimal control strategies.
Keywords: Applied Mathematics; Management Science and Operations Research; Control and Optimization

A Survey of Methods for Automated Algorithm Configuration - Schede, Elias; Brandt, Jasmin; Tornede, Alexander; Wever, Marcel Dominik; Bengs, Viktor; Hüllermeier, Eyke; Tierney, Kevin (arXiv:2202.01651)
Algorithm configuration (AC) is concerned with the automated search of the most suitable parameter configuration of a parametrized algorithm. There is currently a wide variety of AC problem variants and methods proposed in the literature. Existing reviews do not take into account all derivatives of the AC problem, nor do they offer a complete classification scheme. To this end, we introduce taxonomies to describe the AC problem and features of configuration methods, respectively. We review existing AC literature within the lens of our taxonomies, outline relevant design choices of configuration approaches, contrast methods and problem variants against each other, and describe the state of AC in industry. Finally, our review provides researchers and practitioners with a look at future research directions in the field of AC.

Giant Photoelasticity of Polaritons for Detection of Coherent Phonons in a Superlattice with Quantum Sensitivity - Kobecki, Michal; Scherbakov, Alexey V.; Kukhtaruk, Serhii M.; Yaremkevich, Dmytro D.; Henksmeier, Tobias; Trapp, Alexander; Reuter, Dirk; Gusev, Vitalyi E.; Akimov, Andrey V.; Bayer, Manfred (Physical Review Letters)
Keywords: General Physics and Astronomy

Testing and modeling blast loading of a sandwich structure cored with a bio-inspired (balanus) core - Tuzgel, Firat; Akbulut Irmak, Emine Fulya; Guzel, Erkan; Yucesoy, Atacan; Sahin, Selim; Tasdemirci, Alper; Guden, Mustafa (Thin-Walled Structures)
Keywords: Mechanical Engineering; Building and Construction; Civil and Structural Engineering

Betrieb von Federkraftbremsen bei hohen Gleitgeschwindigkeiten - Schadomsky, Magnus; Zimmer, Detmar (Konstruktion)
Federkraftbremsen sind weit verbreitete Komponenten der Antriebstechnik, ansteigend mit abnehmender Größe erreichen sie aktuell Drehzahlen von bis zu 5 000 min−1. Es besteht ein Trend zu schnell laufenden Antrieben, mit Drehzahlen von 10 000 min−1 und darüber. Bisher sind wenig Kenntnisse über das Verhalten des Reibwerts und -moments herkömmlicher Federkraftbremsen mit kostengünstigen organischen Reibbelägen bei diesen Einsatzbedingungen bekannt. Daher wurde ein Prüfstand entwickelt, der die Untersuchung bei Gleitgeschwindigkeiten von bis zu 50 m/s bei verschiedenen Lastträgheiten ermöglicht. Die Versuche zeigten, dass bei begrenzten Reibarbeiten die herkömmliche Federkraftbremse durchaus das Nennbremsmoment bei höheren Gleitgeschwindigkeiten erreicht.
Keywords: Federkraftbremse; Gleitgeschwindigkeit

Ammonium enables reversible aqueous Zn battery chemistries by tailoring the interphase - Ma, Lin; Pollard, Travis P.; Zhang, Yong; Schroeder, Marshall A.; Ren, Xiaoming; Han, Kee Sung; Ding, Michael S.; Cresce, Arthur V.; Atwater, Terrill B.; Mars, Julian; Cao, Longsheng; Steinrück, Hans-Georg; et al. (One Earth)
Keywords: Earth and Planetary Sciences (miscellaneous); General Environmental Science

Supporting Young Immigrants in Their Transition From School to Work? A Staff Perspective on Challenges of Vocational Integration Classes - Goller, Michael (International Journal for Research in Vocational Education and Training)
Context: The implementation of successful measures to support immigrants' integration in cultural, social, and economic life can be considered as one of today's greatest challenges for many societies. This is especially true for adolescent immigrants who have not yet been able to finish education or gain qualifications relevant to joining the labour market. That is why many receiving countries have developed and implemented special programmes that aim at supporting immigrants' integration by facilitating their employability. Unfortunately, not much is known about the process of implementing these programmes or about how education systems, schools, and teachers are dealing with the new situation and target group. In this contribution, the implementation, development, and challenges of German Vocational Integration Classes (VIC), as an example of comparable programmes in the EU, are investigated to address this research gap. The paper considers the following exploratory research questions: (a) What challenges have been experienced by teachers and social workers in the implementation of VIC as well as in the integration of immigrants into the labour market in recent years? (b) How can these challenges be met in the long run and how should VIC be developed to better achieve its aims? Methods: To answer these questions, a sequential qualitative study containing questionnaire and interview elements was conducted. First, teachers and social workers involved in VIC filled in a questionnaire about their experiences and experienced challenges in implementing VIC (N = 46). Then, supplementing interviews were conducted with participants from the first sample in order to generate further insights and to contextualise the findings from the first study part (N = 14). Findings: From the respondents' answers, it appears that the VIC programme is well implemented. The results show, however, that central challenges continue to exist. This concerns, for example, legal regulations or the development of adequate curricula, but also the scope and quality of language education. In addition, problems have also been identified with regard to students' culture-specific education and their individual attitudes. These prevailing problems seem to affect schooling and educational processes. In addition, respondents report feeling left alone to deal with problems and that their experiences from their daily work in VIC and with immigrants are not sufficiently taken into account in policy and school-related decisions. Conclusions: Although VIC seems well implemented, key challenges remain in the view of the participants. It was found that teachers cannot solve many of the identified problems themselves, as they require action at the level of policy or school organisation. For staff, this can be accompanied by increased stress and demotivation. For the young immigrants, the existing challenges can have a long-term impact on school success and transition to vocational education and training. The study thus highlights the importance of targeted and holistic strategies to support immigrant integration through education.
Keywords: Immigration; Educational Policy; Employability; Mixed Methods; VET; Vocational Education and Training; Transitions From Education and Training to Employment

Coalition formation versus free riding in rent-seeking contests - Block, Lukas (Quick And Easy Journal Title)
We study lobby group formation in a two-stage model where the players rst form lobby groups that then engage in a rent-seeking contest to inuence the legislator. However, the outcome of the contest aects all players according to the ideological distance between the implemented policy and the players' preferences. The players can either lobby by themselves, form a coalition of lobbyists or free ride. We nd that free coalition formation is reasonable if either players with moderate preferences face lobby groups with extreme preferences, or if there are two opposing coalitions with an equal number of members. Otherwise, there are always free riders among the players.
Keywords: Group formation; Rent-seeking; Free riding

Quantification of the adhesive coupling of layered structures using guided ultrasonic waves - Nicolai, Marcel; Zeipert, Henning; Lugovtsova, Yevgeniya; Bulling, Jannis; Johannesmann, Sarah; Prager, Jens; Henning, Bernd (Fortschritte der Akustik - DAGA 2022)

Conformal Pressure and Fast-Charging Li-Ion Batteries - Cao, Chuntian; Steinrück, Hans-Georg; Paul, Partha P; Dunlop, Alison R.; Trask, Stephen E.; Jansen, Andrew; Kasse, Robert M; Thampy, Vivek; Yusuf, Maha; Nelson Weker, Johanna; Shyam, Badri; Subbaraman, Ram; et al. (Journal of The Electrochemical Society)
Abstract Batteries capable of extreme fast-charging (XFC) are a necessity for the deployment of electric vehicles. Material properties of electrodes and electrolytes along with cell parameters such as stack pressure and temperature have coupled, synergistic, and sometimes deleterious effects on fast-charging performance. We develop a new experimental testbed that allows precise and conformal application of electrode stack pressure. We focus on cell capacity degradation using single-layer pouch cells with graphite anodes, LiNi0.5Mn0.3Co0.2O2 (NMC532) cathodes, and carbonate-based electrolyte. In the tested range (10 – 125 psi), cells cycled at higher pressure show higher capacity and less capacity fading. Additionally, Li plating decreases with increasing pressure as observed with scanning electron microscopy (SEM) and optical imaging. While the loss of Li inventory from Li plating is the largest contributor to capacity fade, electrochemical and SEM examination of the NMC cathodes after XFC experiments show increased secondary particle damage at lower pressure. We infer that the better performance at higher pressure is due to more homogenous reactions of active materials across the electrode and less polarization through the electrode thickness. Our study emphasizes the importance of electrode stack pressure in XFC batteries and highlights its subtle role in cell conditions.
Keywords: Materials Chemistry; Electrochemistry; Surfaces; Coatings and Films; Condensed Matter Physics; Renewable Energy; Sustainability and the Environment; Electronic; Optical and Magnetic Materials

Corrosion fatigue behavior of electron beam melted iron in simulated body fluid - Wackenrohr, Steffen; Torrent, Christof Johannes Jaime; Herbst, Sebastian; Nürnberger, Florian; Krooss, Philipp; Ebbert, Christoph; Voigt, Markus; Grundmeier, Guido; Niendorf, Thomas; Maier, Hans Jürgen (npj Materials Degradation)
Abstract Pure iron is very attractive as a biodegradable implant material due to its high biocompatibility. In combination with additive manufacturing, which facilitates great flexibility of the implant design, it is possible to selectively adjust the microstructure of the material in the process, thereby control the corrosion and fatigue behavior. In the present study, conventional hot-rolled (HR) pure iron is compared to pure iron manufactured by electron beam melting (EBM). The microstructure, the corrosion behavior and the fatigue properties were studied comprehensively. The investigated sample conditions showed significant differences in the microstructures that led to changes in corrosion and fatigue properties. The EBM iron showed significantly lower fatigue strength compared to the HR iron. These different fatigue responses were observed under purely mechanical loading as well as with superimposed corrosion influence and are summarized in a model that describes the underlying failure mechanisms.
Keywords: Materials Chemistry; Materials Science (miscellaneous); Chemistry (miscellaneous); Ceramics and Composites

Oxide Modified Iron in Electron Beam Powder Bed Fusion—From Processability to Corrosion Properties - Torrent, Christof J. J.; Krooß, Philipp; Huang, Jingyuan; Voigt, Markus; Ebbert, Christoph; Knust, Steffen; Grundmeier, Guido; Niendorf, Thomas (Alloys)
Additive manufacturing (AM) processes are not solely used where maximum design freedom meets low lot sizes. Direct microstructure design and topology optimization can be realized concomitantly during processing by adjusting the geometry, the material composition, and the solidification behavior of the material considered. However, when complex specific requirements have to be met, a targeted part design is highly challenging. In the field of biodegradable implant surgery, a cytocompatible material of an application-adapted shape has to be characterized by a specific degradation behavior and reliably predictable mechanical properties. For instance, small amounts of oxides can have a significant effect on microstructural development, thus likewise affecting the strength and corrosion behavior of the processed material. In the present study, biocompatible pure Fe was processed using electron powder bed fusion (E-PBF). Two different modifications of the Fe were processed by incorporating Fe oxide and Ce oxide in different proportions in order to assess their impact on the microstructural evolution, the mechanical response and the corrosion behavior. The quasistatic mechanical and chemical properties were analyzed and correlated with the final microstructural appearance.

Measurement of material degradation in dependence of shear rate, temperature, and residence time - Schall, Christoph Wilhelm Theodor; Schöppner, Volker (Polymer Engineering and Science)
Keywords: Computing Resources Provided by the Paderborn Center for Parallel Computing

Influence of cutting clearance and punch geometry on the stress state in small punch test - Otroshi, Mortaza; Meschut, Gerson (Engineering Failure Analysis)
The presented paper aims to characterize the damage and fracture behavior of HX340LAD Micro-Alloyed steels using small punch test. Variations with respect to punch geometries and cutting clearance are made to describe the damage behavior of the material under different loading conditions. Experimental investigations are conducted to identify the crack initiation in the specimens. Furthermore, the numerical FEM simulations are performed to identify the stress state at crack initiation. It is shown that different stress states from shear to biaxial tension can be achieved by changing the geometries of punch and varying the cutting clearance. Moreover, it is presented how changing the configurations can influence the stress state variables: Triaxiality and lode angle parameter.
Keywords: Ductile damage; stress state; small punch test; triaxiality; lode angle parameter

Systematisierung einer rechnergestützten Auswertemethode zur Versagensanalyse geklebter Verbindungen - Chudalla, Nick; Teutenberg, Dominik; Meschut, Gerson; Schneider, Miriam; Smart, Dominik (22. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Efficient Frequency Conversion with Geometric Phase Control in Optical Metasurfaces - Reineke Matsudo, Bernhard; Sain, Basudeb; Carletti, Luca; Zhang, Xue; Gao, Wenlong; Angelis, Costantino; Huang, Lingling; Zentgraf, Thomas (Advanced Science)
Keywords: General Physics and Astronomy; General Engineering; Biochemistry; Genetics and Molecular Biology (miscellaneous); General Materials Science; General Chemical Engineering; Medicine (miscellaneous)

Development of a rivet geometry for solid self-piercing riveting of thermally loaded CFRP-metal joints in automotive construction - Vorderbrüggen, Julian; Köhler, Daniel; Grüber, Bernd; Troschitz, Juliane; Gude, Maik; Meschut, Gerson (Composite Structures)
Keywords: Civil and Structural Engineering; Ceramics and Composites

Consideration of the manufacturing history of sheet metal components for the adaptation of a clinching process - Heyser, Per; Wiesenmayer, S; Frey, P; Nehls, T; Scharr, C; Flügge, W; Merklein, M; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
The process chain for the manufacturing of sheet metal components in mass production includes various cutting and forming operations, which influence the resulting properties of the parts and therefore subsequent manufacturing steps, such as clamping and joining. It is shown that clamping of the components leads to superimposed residual stresses and geometry changes. Therefore, the part properties differ from the initial state of the semifinished products, which has to be considered in the design of clinched joints. This paper presents an approach for coupled determination of the properties of semifinished and finished parts during deep drawing and clamping as well as their effects on the joint quality during clinching. One method for the effective and efficient determination of the properties of semifinished products and components during production is using process data from the preceding manufacturing processes, which is concretely presented in this work. In addition to the interconnection of the entire production chain, it is necessary to define relevant process data for each individual manufacturing step and to correlate the data with the material properties reliably. Therefore, the cross-process interactions of different steps of the process chain for the manufacturing of sheet metal components and the effect of process variations on subsequent manufacturing steps are investigated. Consequently, the boundary conditions for a mechanical joining process based on data from preceding process steps can be predicted.
Keywords: Mechanical Engineering; General Materials Science

Self-Adaptive Digital Assistance Systems for Work 4.0 - Yigitbas, Enes; Sauer, Stefan; Engels, Gregor (Digital Transformation: Core Technologies and Emerging Topics from a Computer Science Perspective)

Spin-Orbit Interaction of Light Enabled by Negative Coupling in High-Quality-Factor Optical Metasurfaces - Gao, Wenlong; Sain, Basudeb; Zentgraf, Thomas (Physical Review Applied)
Keywords: General Physics and Astronomy

Output feedback control with prescribed performance via funnel pre-compensator - Lanza, Lukas Johannes (Mathematics of Control, Signals, and Systems)
We study output reference tracking of systems with high relative degree via output feedback only; this is, tracking where the output derivatives are unknown. To this end, we prove that the conjunction of the funnel pre-compensator with a minimum phase system of arbitrary relative degree yields a system of the same relative degree which is minimum phase as well. The error between the original system's output and the pre-compensator's output evolves within a prescribed performance funnel; and moreover, the derivatives of the funnel pre-compensator's output are known explicitly. Therefore, output reference tracking with prescribed transient behavior of the tracking error is possible without knowledge of the derivatives of the original system's output; via funnel control schemes for instance.

Integrating Safety Guarantees into the Learning Classifier System XCS - Hansmeier, Tim; Platzner, Marco (Applications of Evolutionary Computation, EvoApplications 2022, Proceedings)

Bauteilschonendes Entfügen struktureller Klebverbindungen durch Kälte - Chudalla, Nick; Meschut, Gerson; Bartley, Aurélie; Wibbeke, Tim Michael (adhäsion KLEBEN & DICHTEN)
Keywords: Polymers and Plastics; General Chemical Engineering; General Chemistry

Coordinating Amoebots via Reconfigurable Circuits - Feldmann, Michael; Padalkin, Andreas; Scheideler, Christian; Dolev, Shlomi (J. Comput. Biol.)

Environment‐Dependent Stability and Mechanical Properties of DNA Origami Six‐Helix Bundles with Different Crossover Spacings - Xin, Yang; Piskunen, Petteri; Suma, Antonio; Li, Changyong; Ijäs, Heini; Ojasalo, Sofia; Seitz, Iris; Kostiainen, Mauri A.; Grundmeier, Guido; Linko, Veikko; Keller, Adrian (Small)
Keywords: Biomaterials; Biotechnology; General Materials Science; General Chemistry

Experimentelle Untersuchung und Modellvalidierung zur Gravidestillation - Wende, Marc; Fischer, Florian; Kenig, Eugeny (Jahrestreffen der ProcessNet Fachgruppen Fluidverfahrenstechnik und Hochdruckverfahrenstechnik)

Influence of process parameters on the formation of inhalable fiber dust during shredding for mechanical recycling of fiber‐reinforced organo sheets - Hopp, Matthias; Tölle, Lisa (Journal of Applied Polymer Science)

Fiber Dust Formation during the Recycling of FRP - Hopp, Matthias; Tölle, Lisa; Bünger, J.; Westphal, G.; Rosenkranz, N.; Monsé, C. (Kunststoffe international)

Faserstäube beim FVK-Recycling - Hopp, Matthias; Tölle, Lisa; Bünger, J.; Westphal, G.; Rosenkranz, N.; Monsé, C. (Kunststoffe)

Computation on Encrypted Data Using Dataflow Authentication - Fischer, Andreas; Fuhry, Benny; Kußmaul, Jörn; Janneck, Jonas; Kerschbaum, Florian; Bodden, Eric (ACM Transactions on Privacy and Security)
Encrypting data before sending it to the cloud ensures data confidentiality but requires the cloud to compute on encrypted data. Trusted execution environments, such as Intel SGX enclaves, promise to provide a secure environment in which data can be decrypted and then processed. However, vulnerabilities in the executed program give attackers ample opportunities to execute arbitrary code inside the enclave. This code can modify the dataflow of the program and leak secrets via SGX side channels. Fully homomorphic encryption would be an alternative to compute on encrypted data without data leaks. However, due to its high computational complexity, its applicability to general-purpose computing remains limited. Researchers have made several proposals for transforming programs to perform encrypted computations on less powerful encryption schemes. Yet current approaches do not support programs making control-flow decisions based on encrypted data. We introduce the concept of dataflow authentication (DFAuth) to enable such programs. DFAuth prevents an adversary from arbitrarily deviating from the dataflow of a program. Our technique hence offers protections against the side-channel attacks described previously. We implemented two flavors of DFAuth, a Java bytecode-to-bytecode compiler, and an SGX enclave running a small and program-independent trusted code base. We applied DFAuth to a neural network performing machine learning on sensitive medical data and a smart charging scheduler for electric vehicles. Our transformation yields a neural network with encrypted weights, which can be evaluated on encrypted inputs in \( 12.55 \,ms \) . Our protected scheduler is capable of updating the encrypted charging plan in approximately 1.06 seconds.
Keywords: Safety; Risk; Reliability and Quality; General Computer Science

Conditional Beta-Convergence by Gravity - Stöckmann, Nico (Theoretical Economics Letters)

Verteiltes Berechnen kompakter Routingtabellen in Unit Disk Graphen - Hillebrandt, Henning

Realization of Exciton‐Mediated Optical Spin‐Orbit Interaction in Organic Microcrystalline Resonators - Ren, Jiahuan; Liao, Qing; Ma, Xuekai; Schumacher, Stefan; Yao, Jiannian; Fu, Hongbing (Laser & Photonics Reviews)

Controlling exciton distribution in WS2 monolayer on a photonic crystal - Zhang, Xiu; Chen, Zhenshi; Liu, Dong; Wan, Lei; Ma, Xuekai; Gao, Tingge (Applied Physics Express)

Dynamics of phase defects trapped in optically imprinted orbits in dissipative binary polariton condensates - Wingenbach, Jan; Pukrop, Matthias; Schumacher, Stefan; Ma, Xuekai (Physical Review B)

The Ruelle zeta function at zero for nearly hyperbolic 3-manifolds - Cekić, Mihajlo; Delarue, Benjamin; Dyatlov, Semyon; Paternain, Gabriel P. (Inventiones mathematicae)
Abstract We show that for a generic conformal metric perturbation of a compact hyperbolic 3-manifold $$Σ $$ Σ with Betti number $$b_1$$ b 1 , the order of vanishing of the Ruelle zeta function at zero equals $$4-b_1$$ 4 - b 1 , while in the hyperbolic case it is equal to $$4-2b_1$$ 4 - 2 b 1 . This is in contrast to the 2-dimensional case where the order of vanishing is a topological invariant. The proof uses the microlocal approach to dynamical zeta functions, giving a geometric description of generalized Pollicott–Ruelle resonant differential forms at 0 in the hyperbolic case and using first variation for the perturbation. To show that the first variation is generically nonzero we introduce a new identity relating pushforwards of products of resonant and coresonant 2-forms on the sphere bundle $$SΣ $$ S Σ with harmonic 1-forms on $$Σ $$ Σ .
Keywords: General Mathematics

Remote epitaxy of InxGa1-xAs (0 0 1) on graphene covered GaAs(0 0 1) substrates - Henksmeier, T.; Schulz, J.F.; Kluth, E.; Feneberg, M.; Goldhahn, R.; Sanchez, A.M.; Voigt, M.; Grundmeier, Guido; Reuter, Dirk (Journal of Crystal Growth)
Keywords: Materials Chemistry; Inorganic Chemistry; Condensed Matter Physics

Influence of curing-induced pre-deformations on the mechanical properties of adhesively bonded joints in steel-intensive mixed-material structures - Beule, Felix; Teutenberg, Dominik; Meschut, Gerson; Aubel, Tobias; Matzenmiller, Anton (Proceedings of the 6th Conference on Steels in Cars and Trucks)

Early time behavior of spatial and momentum anisotropies in kinetic theory across different Knudsen numbers - Borghini, Nicolas; Borrell, Marc; Roch, Hendrik (arXiv:2201.13294)
We investigate the early time development of the anisotropic transverse flow and spatial eccentricities of a fireball with various particle-based transport approaches using a fixed initial condition. In numerical simulations ranging from the quasi-collisionless case to the hydrodynamic regime, we find that the onset of $v_n$ and of related measures of anisotropic flow can be described with a simple power-law ansatz, with an exponent that depends on the amount of rescatterings in the system. In the few-rescatterings regime we perform semi-analytical calculations, based on a systematic expansion in powers of time and the cross section, which can reproduce the numerical findings.

A review of 100% renewable energy scenarios on islands - Meschede, Henning; Bertheau, Paul; Khalili, Siavash; Breyer, Christian (WIREs Energy and Environment)
Keywords: General Environmental Science; Renewable Energy; Sustainability and the Environment

Even anisotropic-flow harmonics are from Venus, odd ones are from Mars - Bachmann, Benedikt; Borghini, Nicolas; Feld, Nina; Roch, Hendrik (arXiv:2203.13306)
We test the ability of the "escape mechanism" to create the anisotropic flow observed in high-energy nuclear collisions. We compare the flow harmonics $v_n$ in the few-rescatterings regime from two types of transport simulations, with $2→ 2$ and $2→ 0$ collision kernels respectively, and from analytical calculations neglecting the gain term of the Boltzmann equation. We find that the even flow harmonics are similar in the three approaches, while the odd harmonics differ significantly.

Linearly shifting ferromagnetic resonance response of La0.7Sr0.3MnO3 thin film for body temperature sensors - Hou, W; Yao, Y; Li, Y; Peng, B; Shi, K; Zhou, Z; Pan, J; Liu, M; Hu, J (Frontiers of materials science)

Dataset for random uniform distributions of 2D circles and 3D spheres. - Wojciechowski, M (Data Brief)